Using GPR Technique Assessment for Study the Sub-Grade of Asphalt andConcrete Conditions - Mahdi, Alaa (Iraqi Journal of Science, 2025)
The Ground Penetrating Radar (GPR) is frequently used in pavement engineeringfor road pavement inspection. The main objective of this work is to validatenondestructive, quick and powerful measurements using GPR for assessment of subgradeand asphalt /concrete conditions. In the present study, two different antennas(250, 500 MHz) were used. The case studies are presented was carried in Universityof Baghdad over about 100m of paved road. After data acquisition and radar gramscollection, they have been processed using RadExplorer V1.4 softwareimplementing different filters with the most effective ones (time zero adjustment andDC removal) in addition to other interpretation tool parameters.The interpretation results showed that with 250 MHz antenna, the buried plastic pipeand the flexible pavement layer were identified. The later appeared as one layerwithout identifying the rigid pavement layer. With 500 MHz antenna, the plasticpipe, rigid pavement, appeared clearly. Moreover, the short type of maximum timewindow using antenna 500 MHz appeared to be the most suitable for detecting someradar anomalies (plastic pipe, and pavement thickness) which were clearly defined.While, the suitable radar wave velocity was 100 m/ns for estimation of the flexibleand rigid pavement layer thicknesses respectively. No change is obtained withchanging point interval. . Finally, this diagnostic tool of GPR for pavement defectsand damages investigations seems very promising, cost effective and efficient in itsimplementation.